Urban rivers in Belgrade, Serbia. Radical transformations and illegal urban practices in a post-socialist capital - Sanja Iguman (Archivio Antropologico Mediterraneo)
The present paper focuses on the area of the Serbian capital marked off by two transnational rivers, the Sava and the Danube and by their confluence, which determined the birth and development of Belgrade. This area, target of radical and illegal urban transformations in the last decade, is analysed focusing on local activist groups’ engagements and their reactions to these dynamics. The case explored is a specific place in Belgrade: river Sava and the banks in the vicinity of the confluence. This is a perfect example of landscape intended as a multi-layered concept that connects natural resources, human-made elements and most important – the people and their movements, actions, narration, emotions and relations. The paper describes how this place has been transformed through time, in cultural, ecological and physical sense, and it will mostly analyse the social consequences that the mentioned transformations have left on local citizens and on the way they are reacting to that, gathered in the neighbourly, activist groups.